Prediction of Hydrate Dissociation Conditions in Natural/Acid/Flue Gas Streams in the Presence and Absence of Inhibitors - Ismail Ismail; Vassilis Gaganis (Materials Proceedings, 2024)
Accurate predictions of hydrate dissociation conditions are of paramount importance for optimizing mitigation strategies and preventing hydrate formation in oil and gas operations. These predictions are crucial for selecting appropriate thermodynamic inhibitors, reducing operating costs, and minimizing environmental impact. Moreover, they facilitate the practical application of innovative hydrate technologies such as energy storage, gas separation, and carbon capture. To address this need, various commercial PVT software packages, such as MultiFlash, HydraFLASH, CSMGem, and CSMHyd, are commonly used. However, these packages employ different computational approaches, including hydrate modeling, equations of state (EoS), and phase behavior representation, which can influence their prediction capabilities. To assess their accuracy, we conducted an evaluation using a comprehensive database of 400 experimental dissociation pressure data points from both uninhibited and inhibited hydrate former systems. Through our evaluation, we identified the unique strengths and weaknesses of each software package, providing valuable guidance for industry practitioners and researchers who aim to accurately predict hydrate stability conditions, enabling them to implement effective mitigation strategies and exploit technological solutions.